Governmentality : power and rule in modern society - Dean, Mitchell, 1955- (SAGE, 2010)
"With its emphasis on the relationship between governmentality and other key concepts drawn from Michel Foucault, such as bio-politics and sovereignty, the first edition anticipated and defined the terms of contemporary debate and analysis." "In this timely second edition Mitchell Dean engages with the full textual basis of Foucault's lectures and once again provides invaluable insights into the traditions, methods and theories of political power identifying the authoritarian as well as liberal sides of governmentality." "Many of the chapters have been revised and updated to incorporate, and respond to, new theoretical, social and political developments in the field; a new introduction surveying the state of governmentality today has also been added as well as a completely new chapter on international governmentality and a postscript on the crisis of neo-liberalism today."--BOOK JACKET.